Design, Manufacturing, and Comparative Analysis of a Mini Extruder for Polymer Flow Characterization: A Case Study on HDPE and PMMA Polymers - Emin Uslu; Galip Yılmaz (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Polymer extrusion is one of the most widely used polymer processing methods and the sole option for many standard products. The modern extrusion machine has a very sophisticated design; for example, the extrusion screw has different zones and complex geometry. Determining the proper processing settings is always a challenge for engineers. Additionally, complex rheological properties of the polymers in extrusion sometimes yield challenging and unpredictable problems to troubleshoot. For convenience, a small-scale extrusion machine can be used to troubleshoot and analyze the polymers rather than the large manufacturing machines that are hard to work with. This study has produced a small-scale extrusion machine that is easy to manufacture without deviating from the extrusion process's nature. The extruder, whose production details are given, was tested with two different polymers: HDPE and PMMA. The correct temperature and screw rotation speed were determined with the extruder for the proper process parameters. In addition, the temperature-viscosity relationship of the polymers' flow nature was also determined.